Is Thyroidectomy in Patients with Hashimoto’s Thyroiditis More Risky? - McManus, Catherine (2012)
BACKGROUND: Hashimoto’s thyroiditis (HT) is an organ –specific autoimmune disease characterized by production of antibodies such as anti-thyroperoxidase (TPO), which leads to destruction of the thyroid gland and a decrease in normal thyroid function. Thyroidectomy is performed when the patient presents with symptoms or when potential neoplastic degeneration occurs; however, surgery can be difficult due to the dense inflammatory process around the thyroid gland. We hypothesized that patients with HT may have a higher rate of complications following thyroid surgery. METHODS: We identified 1791 consecutive patients who underwent thyroidectomy from May 1994 to December 2009. Patients with HT were compared to without HT with regard to outcomes with ANOVA and Chi-squared (SPSS, Inc.). RESULTS: Patients with HT were significantly younger and more likely to be female. There was no significant difference between the two groups in the rate of malignancy. However, patients undergoing thyroidectomy with HT had a significantly higher postoperative complication rate. Specifically, the rates of overall complications, transient complications, and permanent complications were all increased in HT patients. CONCLUSION: Patients with HT had a higher rate of complications after thyroidectomy when compared to patients without HT. Therefore, careful consideration must be taken prior to pursuing operative treatment in patients with HT including providing adequate informed consent regarding the increased risks of surgery.